On k-Gamma and k-Beta Distributions and Moment Generating Functions. (15th July 2014) - Rahman, Gauhar; Mubeen, Shahid; Rehman, Abdur; Naz, Mammona
Abstract : The main objective of the present paper is to define k -gamma and k -beta distributions and moments generating function for the said distributions in terms of a new parameter k > 0 . Also, the authors prove some properties of these newly defined distributions.